Biomolecular endotype factors involved in COVID-19 airway infectivity: A systematic review. Issue 1 (February 2021) - Jain, Neil; Varman, Rahul; Tarbox, James A.; Nguyen, Tam
Abstract: Objectives: To review the current knowledge of biomolecular factors surrounding otorhinolaryngeal illnesses and analyze their presence in COVID-19 virulence. Emphasis was placed on cytokines and vitamin D for determining susceptibility of illness. Methods: A primary literature search of PubMed and Google Scholar for articles published between January 1, 2002 to May 31, 2020, was performed without language restrictions from May 8, 2020 to May 31, 2020. A focused second search was conducted from October 31, 2020 to November 2, 2020 for articles published between January 1, 2002 to October 31, 2020. Eligible articles were selected after evaluation of titles, abstracts, and references. A total of 45 were included in this review. Results: Differing endotype classification schemes are used to determine cytokines present in chronic rhinosinusitis, asthma, and allergies. While immunologic responses and biomarkers are primary methods of differentiation, recent literature has also implicated geographic distribution of chronic rhinosinusitis patients in accounting for cytokine variations. The cytokines of interest (IL-4, IL-13, and INF-γ) present in the endotypes of these conditions may point towards protective mechanisms against COVID-19 through downregulation of the ACE2 receptor. These cytokines and Vitamin D highlight new areas of study for factors affecting SARS-CoV-2 virulence. Conclusions: Further research is needed to understand the effects of Vitamin D and the various cytokines prevalent among endotypes of nasal/pharyngeal illnesses on COVID-19 pathogenesis. Findings may point towards epidemiologic trends of SARS-CoV-2 transmission and have future therapeutic indications.